Strain Accumulation and Microstructural Evolution During Friction Stir Welding of Pure Magnesium - Li, Zhuoliang; Ding, Hua; Chen, Yu; Li, Jizhong; Liu, Lizhong (Frontiers in Materials, 2020)
In this study, the stain accumulation during friction stir welding of pure Mg was predicted and verified at different rotation speeds, together with the detailed microstructural evolution. The results indicate that the strain accumulation can be divided into three stages: 1) acceleration flow, 2) high velocity flow, and (III) decelerate and constant velocity flow. The rate of strain accumulation was relatively low at both stage I and stage III, while it became extremely high at stage III. The higher the speed of rotation, the severe plastic deformation more easily occurred within the material. The accumulated strain of pure Mg were determined to be approximately 12.8 and 14.5 at the rotation speed of 1,000 and 1,500 rpm, respectively. Relatively believable equations were established by calculation and derivation. In addition, the microstructural evolution shows that that the friction stir welding processed pure Mg first experienced significant grain refinement during plastic deformation but led to an obvious grain growth at the later stage due to the heat effect by high temperature field.